Effects of hearing aids in the balance, quality of life and fear to fall in elderly people with sensorineural hearing loss - Lacerda, Clara Fonseca; Silva, Luciana Oliveira e; de Tavares Canto, Roberto Sérgio; Cheik, Nadia Carla (International Archives of Otorhinolaryngology, 2012)
Introduction: The aging process provokes structural modifications and functional to it greets, compromising the postural control and central processing. Studies have boarded the necessity to identify to the harmful factors of risk to aged the auditory health and security in stricken aged by auditory deficits and with alterations of balance.Objective: To evaluate the effect of auditory prosthesis in the quality of life, the balance and the fear of fall in aged with bilateral auditory loss.Method: Carried through clinical and experimental study with 56 aged ones with sensorineural auditory loss, submitted to the use of auditory prosthesis of individual sonorous amplification (AASI). The aged ones had answered to the questionnaires of quality of life Short Form Health Survey (SF-36), Falls Efficacy International Scale- (FES-I) and the test of Berg Balance Scale (BBS). After 4 months, the aged ones that they adapted to the use of the AASI had been reevaluated.Results: It had 50% of adaptation of the aged ones to the AASI. It was observed that the masculine sex had greater difficulty in adapting to the auditory device and that the variable age, degree of loss, presence of humming and vertigo had not intervened with the adaptation to auditory prosthesis. It had improvement of the quality of life in the dominance of the State General Health (EGS) and Functional Capacity (CF) and of the humming, as well as the increase of the auto-confidence after adaptation of auditory prosthesis.Conclusion: The use of auditory prosthesis provided the improvement of the domains of the quality of life, what it reflected consequently in one better auto-confidence and in the long run in the reduction of the fear of fall in aged with sensorineural auditory loss.
Keywords: hearing loss; quality of life; postural balance